Using legumes as indicators in the seasonally dry vegetation types in South America. (February 2017) - Lima, Jacira R.; Santos, Nivea D.; Tozzi, Ana M.G.A.; Mansano, Vidal F.
Highlights: We examined diversity of Leguminosae species (trees and shrubs) along of seasonal vegetation types in South America. We identified 72 indicators species for seven floristic units which, in general, includes areas with the same type of vegetation and supports the existing classification systems. The conservation of the seasonal vegetation types in South America is still inefficient. We found a larger number of areas with high biological importance for conservation (high species diversity and restricted species), located outside of protected areas. We suggest that an area of approximately 1, 796, 256 km 2 indicated as highly biologically important for Leguminosae species (trees and shrubs) should be considered as priorities for future conservation and management measures. Abstract: The South American corridor of seasonally dry vegetation (SACSV) includes different types of physiognomies forming a continuous corridor with high biodiversity and endemism; however, little attention has been paid to the conservation of the SACSV. As this is an area with great diversity, cataloguing all the species is challenging. Thus, we suggest the use of Leguminosae species (trees and shrubs) as bioindicators of the different types of vegetation present in the area and to identify priority areas for conservation of the SACSV, since the family is highly represented in this vegetation. The study area was divided into 358 grid cells with recorded specimens. For each grid cell, species richness, taxonomic diversity, number of species restricted to one type of vegetation, and threatened and indicator species of phytogeographic domain were calculated. To determine the phytogeographic domains and indicator species, analysis of similarity, cluster and indicator species (ISA) were performed. The results show that 43% of the grid cells (154) have high biological importance for conservation (high taxonomic diversity, species richness and number of restricted species), all of which lie outside of protected areas. We identified 72 indicator species for seven floristic units, which, in general, include areas of the same phytogeographic domain, supporting the existing classification systems. We suggest that for effective conservation of biodiversity present in the SACSV, it is necessary to establish protected areas throughout the SACSV.